Evaluation of patients’ functioning after treatment for testicular malignant germ cell tumour – own experience - Osmańska, Maria; Kawiecka-Dziembowska, Bożena; Tujakowski, Jerzy; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2008)
Aim of the study: We assessed the health status, interpersonal relationships, family and social functioning, and sexual dysfunction in men after treatment for testicular cancer (TC). Material and methods: The study was performed in 2004. 70 men treated for TC in the Centre of Oncology in Bydgoszcz were invited to the examination. The patients had complete remission of disease for at least six months. The study instrument was a self-report questionnaire concerning items on current general health status, occupation, social support, family and social life, and sexual functioning after oncological treatment. Results: 53 patients (range 21–65 years) returned a completed questionnaire. All men underwent orchidectomy; afterwards 37 patients underwent chemotherapy (CHTH), 6 patients retroperitoneal lymph node dissection (RPLND), 4 patients radiotherapy (RTH), 4 men remained under surveillance, 1 patient received CHTH + RTH and 1 patient CHTH + RPLND. Almost 80% of patients assessed their health status as good or very good. Most men associated the complaints with the cancer treatment. 85% of men felt fear of disease relapse. 43% of patients had retired because of TC. The disease influenced private life for above half of men participating in the study. 83% of patients assessed their sexual life as successful. 25% of men reported decrease of sexual desire, over 17% reported decrease of sexual satisfaction, about 28% of patients reported erectile disorders, about 24% of study men reported ejaculation disorders, and 6% of patients reported loss of orgasm. We did not find a correlation between sexual dysfunctions and treatment regimens, and disease staging and age of the study men . Conclusions: The present study results were similar to those reported in the literature except that our patients had a high level of fear of disease relapse and a large number had retired after treatment for TC.